The Effects of pH-Neutral Electrolysed Oxidising Water on Growth and Development of Chrysanthemums - Šušek, Andrej; Copot, Klara; Šiško, Metka (Agricultura Scientia, 2021)
The aim of the study was to analyse the effects of pH-neutral electrolysed oxidising water (pH-neutral EOW), prepared by using the Envirolyte® system, on the growth and development of chrysanthemums. The experiment included two varieties of potted ('Tonka Blanc', 'Jahou CoCo') and two cut flower varieties of chrysanthemums ('Annecy White', 'Ninja'). The test plants planted in pots were irrigated with three different solutions of pH-neutral EOW (0%, 0.1% and 0.2%). Based on the results of the study, we can confirm that pH-neutral EOW has a significant effect on the growth and development of the studied chrysanthemum varieties. In potted chrysanthemums, we found a significant effect on the increased number and diameter of inflorescences, as well as fresh and dried weight of the plant and inflorescences. Chrysanthemums for cut flowers were taller and more developed, with a greater weight of the aboveground part of the plant. Its effect on the growthand development of the studied varieties depended on the solution of the mixture. Best results were observed with the 0.2% solution of pH-neutral EOW.